Five steps in leukocyte extravasation in the microcirculation by chemoattractants - T. Oda; M. Katori; K. Hatanaka; S. Yamashina (Hindawi Limited, 1992)
For in vivo study of the phenomena observed in vitro, PMN (polymorphonuclear leukocyte) extravasation was analysed quantitatively in the microcirculation of the hamster cheek pouch using a video system. Topical application of leukotriene B4 or N-formyl-methionylleucyl- phenylalanine increased dose dependently the number of PMNs adhering to the venules. Eighty to 90% of the adhering PMNs disappeared from the vascular lumen into the venular wall within 10-12 rain after the adhesion. After PMNs had passed through the endothelial cell layer, they remained in the venular wall for more than 30 min after application of the chemoattractants and appeared in the extravascular space. Thus, the process could be divided into five steps: (1) rolling and (2) adhesion to the endothelium, (3) passage through the endothelial layer (4) remaining in the venular wall, and (5) passage through the basement membrane.